Ultrafast Nanophotonics and Opto-Electronics: From All-Optical Switching Based on Metamaterial-Cavity Electrodynamics to Plasmon-Driven Polaritonic Chemistry - Maccaferri, Nicolo (Conference on Lasers & Electro-Optics Europe & International Quantum Electronics Conference (Online), 2023)
Ultrafast control of light-matter interactions is fundamental to mark new technological frontiers, for instance in light-driven information processing and nanoscale photochemistry [1]. In this context, we have explored the possibility to use metal-dielectric nanocavities to achieve all-optical modulation of light reflectance. Without the need of driving higher order effects, our system is based on linear absorption, provides large relative modulation exceeding 100% and switching bandwidths of few hundred GHz at moderate excitation fluence [2]. This archetypical system becomes even more interesting if the dielectric inclusion is not just a "passive" insulator material but an inorganic van der Waals bonded semiconductor, like a transition metal dichalcogenide (TMD). TMDs are subject of intense research due to their electronic and optical properties which are promising for next-generation opto-electronic devices. In this context, understanding ultrafast carrier dynamics, as well as charge and energy transfer at the interface between metals and semiconductors, is crucial and yet quite unexplored. By employing a pump-push-probe scheme, we experimentally study how optically-induced thermionic charge carrier injection affects the exciton formation dynamics in bulk WS 2 [3], disclosing excellent opportunities also in nano-chemistry. In fact, if an electronic transition (e.g., exciton or more simply a singlet) strongly interacts with the optical modes of a resonator, we can tailor the energetics and the morphology of a molecular state. By combining quantum mechanical modelling and pump-probe spectroscopy, we shed light on the ultrafast dynamics of a hybrid system composed of photo-switchable dye molecules coupled to optically anisotropic plasmonic nanoantennas, which allow us to selectively switch between two regimes where the light-matter interaction is either weak or strong [4]. Our synergistic approach is thus instrumental to devise new strategies for tailoring electronic states by using plasmons for applications in polaritonic chemistry on femtosecond timescales.